SINGLE COMPLETE DENTURE PADA PASIEN HISTERICAL DENGAN KETERBATASAN MENGONTROL GERAKAN LIDAH (LAPORAN KASUS) - Arnefi Arnefi; Henni Koesmaningati (Faculty of Dentistry, Universitas Indonesia, 2015)
Good cooperation between patient and the dentist is needed in full denture fabrication. This case report presents problems that occurred when the dentist had to face a hysterical patient with uncontrolled tongue movement. The probles include patient's dentispsychological state that showe hesitant towards the dentist. In this case, the patient already had two pairs or full dentures when seeking for another one. The second problem was related to the uncontrolled tongue movement, which could decrease lower denture stability. The dentist had to be very patient in listening to patient's complaints and assure the patient to adjust with the new dentures.